(untitled) (Herald of Journalism, 2020)
Study the transformation of film language in the Kazakh feature film era of independence shows that domestic films gradually, but until spon taneously proceeds to create its system of signs movie simulating Kazakh mythology of modern culture. However, it is not complicated system leads to slurred reflection of today’s reality in the modern Kazakh cinema. Today has matured the need to rethink the inner nature of a feature film with a historical past to the present day, the need to purposefully engage in the construction of the fine film. The original path of development is not to deny the European, Asian, etc. Finemaking, and use them as an inevitable stage in the formation of their own, original system cinematic alphabet characters first movie and try to join and work on that basis its own alphabet cinema.